Conservation-restoration treatment of oriental manuscripts Aṭ-Ṭāriqa al-Muḥammadiyya - Nejra Ljubuškić (Bosniaca, 2023)
This paper represents the conservation-restoration process of the oriental manuscript in the Turkish language, Aṭ-Ṭāriqa al-Muḥammadiyya. The manuscript is stored in the library of the Tekke Mesudija which has very important old and rare book materials, among which oriental manuscripts hold a special place. The goal of the restoration was to restore the functionality of the binding and preserve the texts. The restoration treatments included: mechanical and chemical cleaning of the pages, repairing a missing portion of a page with Japanese paper, sewing the forms into the bookblock, embroidering the endband, and restoring the original covers. Conservation-restoration documentation with a proposal on the handling and preventive conservation of manuscripts was also prepared.